2022
DOI: 10.1177/0271678x221142527
|View full text |Cite
|
Sign up to set email alerts
|

Directional sensitivity of dynamic cerebral autoregulation during spontaneous fluctuations in arterial blood pressure at rest

Abstract: Directional sensitivity, the more efficient response of cerebral autoregulation to increases, compared to decreases, in mean arterial pressure (MAP), has been demonstrated with repeated squat-stand maneuvers (SSM). In 43 healthy subjects (26 male, 23.1 ± 4.2 years old), five min. recordings of cerebral blood velocity (bilateral Doppler ultrasound), MAP (Finometer), end-tidal CO2 (capnograph), and heart rate (ECG) were obtained during sitting (SIT), standing (STA) and SSM. A new analytical procedure, based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 50 publications
1
22
3
Order By: Relevance
“…Each of these conditions might have been responsible for the elimination of five to seven subjects only, but when combined, the overall number grew to 40. Despite this reduction in sample size, the remaining number of 46 male and 58 female subjects was above the minimum sample sizes that we had previously estimated to detect the presence of directional sensitivity, in the worst case of n ¼ 38, for participants at rest in the sitting position, 8 and led to highly significant differences between ARI þD and ARI -D (Table 2). Nevertheless, future studies are needed to improve the reliability of estimates of directional sensitivity with the ARMA or alternative approaches, to minimize the rate of rejections, mainly when aiming to perform clinical studies of different cerebrovascular conditions.…”
Section: Methodological Considerationsmentioning
confidence: 89%
See 3 more Smart Citations
“…Each of these conditions might have been responsible for the elimination of five to seven subjects only, but when combined, the overall number grew to 40. Despite this reduction in sample size, the remaining number of 46 male and 58 female subjects was above the minimum sample sizes that we had previously estimated to detect the presence of directional sensitivity, in the worst case of n ¼ 38, for participants at rest in the sitting position, 8 and led to highly significant differences between ARI þD and ARI -D (Table 2). Nevertheless, future studies are needed to improve the reliability of estimates of directional sensitivity with the ARMA or alternative approaches, to minimize the rate of rejections, mainly when aiming to perform clinical studies of different cerebrovascular conditions.…”
Section: Methodological Considerationsmentioning
confidence: 89%
“…22 To assess the directional sensitivity of dynamic CA at rest, separate estimates of the integrated positive (MAP þD ) and negative (MAP ÀD ) derivatives of MAP are needed, as described in detail previously. 8 In short, the numerical derivatives of MAP are calculated using a 5-sample moving window, then separated into their positive and negative values. The positive and negative derivatives are integrated separately and the linear trends were removed by linear regression, generating the MAP þD and MAP ÀD signals that are then taken as the two separate inputs to the MCAv output.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that males and females have different middle cerebral blood velocities during both poikilocapnia and hypercapnia, suggesting sex can influence cerebral hemodynamics. 52 A review written by Cheryl D Bushnell et al indicates that biologic sex affects many variables that are important to stroke, such as general health status, cerebrovascular anatomy and function, unique risk factors (such as pregnancy and preeclampsia), symptomatology, and therapeutic response. 53 Sex also has impact on the therapeutic efficacy of drugs for stroke.…”
Section: Discussionmentioning
confidence: 99%